2017
DOI: 10.4269/ajtmh.16-1000
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Direct Membrane and Direct Skin Feeding Assays for Plasmodium falciparum Transmission-Blocking Vaccine Trials in Bancoumana, Mali

Abstract: Malaria transmission-blocking vaccines (TBV) have been evaluated in field trials in Mali since 2013. However, the assays currently used to measure serum antibody TB activity (TBA) after vaccination are highly variable, in part due to the lack of optimization and standardization for field assays in which mosquitoes feed on gametocytemic blood. Herein, we report a study conducted in Bancoumana village, Mali, where we identify and optimize the parameters that contribute to successful mosquito feeding outcomes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…These DSF assays use a line of locally caught Anopheles coluzzii recently adapted for breeding in a contained insectary. In these studies [52], uninfected mosquitoes (generally 30-60 per assay) are fed on study volunteers on a regular basis during the malaria transmission season, with the expectation that an effective vaccine will reduce the number of infected mosquitoes compared to controls. We believe DSFs, in which insectary-raised clean mosquitoes are directly fed on infected individuals, may be more likely to be predictive of an intervention's impact on transmission than membrane feeds.…”
Section: Measuring Vaccine Activitymentioning
confidence: 99%
“…These DSF assays use a line of locally caught Anopheles coluzzii recently adapted for breeding in a contained insectary. In these studies [52], uninfected mosquitoes (generally 30-60 per assay) are fed on study volunteers on a regular basis during the malaria transmission season, with the expectation that an effective vaccine will reduce the number of infected mosquitoes compared to controls. We believe DSFs, in which insectary-raised clean mosquitoes are directly fed on infected individuals, may be more likely to be predictive of an intervention's impact on transmission than membrane feeds.…”
Section: Measuring Vaccine Activitymentioning
confidence: 99%
“…Coulibaly and colleagues compared the feeding rate for An. coluzzii mosquitoes between 3 days and 9 days post emergence and found that 3 day old mosquitoes had a signi cantly higher feeding rate compared to 6 and 9 day old mosquitoes [10].…”
Section: Introductionmentioning
confidence: 96%
“…Starving conditions is a key component that greatly impacts mosquito feeding rates and a balance needs to be established between starving the mosquitoes for too long, thereby increasing mosquito mortality or affecting their tness [10], and not starving for long enough so mosquitoes only partly feed or not at all.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations